Effect of non-invasive rhythm control on outcomes in patients with first diagnosed atrial fibrillation presenting to an emergency department - Christian Salbach; Mustafa Yildirim; Hauke Hund; Matthias Müller-Hennessen; Norbert Frey; Hugo Anton Katus; Evangelos Giannitsis; Barbara Ruth Milles (BMC Emergency Medicine)
Abstract Background Evidence suggests a benefit of a rhythm control approach in patients with a recent diagnosis of atrial fibrillation (AF). This study sought to evaluate clinical characteristics, treatment strategies and outcomes in patients with first diagnosed AF (FDAF) undergoing a non-invasive rhythm control strategy in an emergency department (ED). Methods This analysis uses data from the Heidelberg Registry of Atrial Fibrillation (HERA-FIB). HERA-FIB is a retrospective single-centre observational study which consecutively included patients presenting to the ED of the University Hospital of Heidelberg between June 2009 and March 2020 with a sequential follow-up for all-cause mortality, stroke, major bleeding events and myocardial infarction (MI). Outcomes of patients with FDAF were related to treatment strategy (non-invasive rhythm vs. rate control). Results Among the 2,758 (27%) patients who presented with FDAF, a non-implementation of a non-invasive rhythm control strategy at admission was observed in 75.4% and associated with an excess of all-cause mortality hazard ratio (HR): 1.61 (95%CI 1.30–1.99), p < 0.0001 and incident MI HR: 1.88 (95% CI 1.22–2.90), p = 0.0043 during follow-up. The non-implementation of a non-invasive rhythm control remained an independent predictor for all-cause mortality and MI even after adjustment for significant univariate variables with an adjusted HR of 1.52 (95%CI: 1.14–2.04, p = 0.0043) and 1.89 (95%CI: 1.03–3.45, p = 0.0392), respectively. Conclusion Real-world data from FDAF patients presenting to an ED showed a benefit regarding all-cause mortality and MI favouring a non-invasive rhythm control strategy. Further prospective research is needed to validate this hypothesis. Trial registration The trial was registered at ClinicalTrials.gov Identifier: NCT05995561.